Coverage repair strategies for wireless sensor networks based on muti-mobile nodes and genetic algorithm - Miao YE; Yu-ping WANG; Jing-xuan WEI (Tongxin xuebao)
A repairing strategy for the coverage of the sensor network based on multi-mobile nodes and path planning is designed.Such mechanism can ultimately repair common nodes in a timely fashion via energy consumption analysis of the nodes by using genetic algorithm to calculate the reasonable moving path of the mobile nodes,which can avoid cov-erage holes caused by the death of sensor nodes at its best.The global convergence the designed algorithm is proved by stochastic process.Simulation experiments have proven the effectiveness of the designed mechanism and the relevant solution algorithm.